Krisis Pembelajaran Bermakna dan Integratif terhadap Penghayatan Nilai-Nilai Keagamaan Peserta Didik di MTs N 1 Banggai - Mohammad Ariswara Rai Djafar; Najamudin Petta Solong; Munira Munira; Fatimah Djafar (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The digital transition at MTs N 1 Banggai has fundamentally altered student learning behaviors, leading to a